2002
DOI: 10.1073/pnas.152112399
|View full text |Cite
|
Sign up to set email alerts
|

Reduced fear expression after lesions of the ventral hippocampus

Abstract: The hippocampus has a critical role in several fundamental memory operations, including the conditioning of fear to contextual information. We show that the hippocampus is necessary also for unconditioned fear, and that the involved circuitry is at the ventral pole of the hippocampus. Rats with selective hippocampal lesions failed to avoid open arms in an elevated plus-maze and had decreased neuroendocrine stress responses during confinement to a brightly lit chamber. These effects were reproduced by lesions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
576
5
9

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 776 publications
(626 citation statements)
references
References 45 publications
(60 reference statements)
36
576
5
9
Order By: Relevance
“…This hypothesis is consistent with the idea that the ventral hippocampus plays a more important role in unconditioned anxiety than the dorsal hippocampus, which is based on wide range of evidence Bannerman et al, 2004;Pentkowski, et al, 2006;Engin & Treit, 2007). More specifically, ventral cytotoxic lesions have been found to cause more pronounced anxiolytic effects than dorsal lesions on a variety of measures of innate anxiety, including elevated plus maze measures (Kjelstrup et al, 2002;Bannerman et al, 2002Bannerman et al, , 2004, and ventral infusion of the local anaesthetic lidocaine (a sodium channel blocker inactivating neurons and fibers of passage) significantly increased the proportion of open-arm entries on the elevated plus maze test, whereas dorsal lidocaine had no significant effect (Bertoglio et al, 2006). Moreover, ventral, but not dorsal, hippocampal muscimol reduced unconditioned fear, as assessed by the shock-probe burying test (McEown and Treit, 2010).…”
Section: Introductionsupporting
confidence: 88%
See 3 more Smart Citations
“…This hypothesis is consistent with the idea that the ventral hippocampus plays a more important role in unconditioned anxiety than the dorsal hippocampus, which is based on wide range of evidence Bannerman et al, 2004;Pentkowski, et al, 2006;Engin & Treit, 2007). More specifically, ventral cytotoxic lesions have been found to cause more pronounced anxiolytic effects than dorsal lesions on a variety of measures of innate anxiety, including elevated plus maze measures (Kjelstrup et al, 2002;Bannerman et al, 2002Bannerman et al, , 2004, and ventral infusion of the local anaesthetic lidocaine (a sodium channel blocker inactivating neurons and fibers of passage) significantly increased the proportion of open-arm entries on the elevated plus maze test, whereas dorsal lidocaine had no significant effect (Bertoglio et al, 2006). Moreover, ventral, but not dorsal, hippocampal muscimol reduced unconditioned fear, as assessed by the shock-probe burying test (McEown and Treit, 2010).…”
Section: Introductionsupporting
confidence: 88%
“…Studies examining the effects of lesion or pharmacological manipulations of the hippocampus in rats have provided compelling evidence that the hippocampus is important for unconditioned anxiety/fear responses, as well as the formation and expression of conditioned fear responses to elemental (e.g., auditory) and contextual stimuli 1 Moreover, the weight of evidence from studies using separate ventral or dorsal hippocampal manipulations suggests that the ventral hippocampus plays a rather general role in unconditioned anxiety and conditioned fear, whereas dorsal hippocampal contributions are more restricted to specific mnemonic aspects of fear conditioning, such as context learning; this is consistent with the ventral hippocampus featuring stronger direct connectivity to amygdala and hypothalamus, key components of the brain's anxiety and fear circuit, whereas the dorsal hippocampus is more closely linked to parts of the entorhinal cortex that are implicated in visuo-spatial information encoding (Moser & Moser, 1998;Anagnostaras et al, 2001;Bast et al, 2001b;Kjelstrup et al, 2002;Bannerman et al, 2004;Maren & Holt, 2004;Pentkowski, et al, 2006;Bast, 2007;Engin & Treit, 2007;Fanselow & Dong, 2010;Bast, 2011). …”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…Increased expression of NPY (which also has anticonvulsant features; Richichi et al, 2004) in the hippocampus may also help in explaining the slower dentate gyrus kindling rate in betamethasone-exposed immature rats compared to saline-exposed rats in our previous study (Velíšek, 2005b). Earlier studies have shown that mainly ventral but also dorsal hippocampus is involved in anxiety control (Andrews et al, 1997;Bannerman et al, 2002aBannerman et al, , b, 2003Gonzalez et al, 1998;Kjelstrup et al, 2002;McHugh et al, 2004) and NPY alterations in the hippocampus affect anxiety behaviors (Heilig, 2004;Thorsell et al, 2000). We did not see an increase in NPY expression in the basolateral amygdala; however, lesion studies have demonstrated that this region does not participate in the anxiety behavior tested in the elevated plus maze (Gonzalez et al, 1996;Treit et al, 1993), and that the amygdala is rather associated with fear control .…”
Section: Technical Considerationsmentioning
confidence: 62%